A Cross Sectional Study On The Relationship Of Maternal Bonding And Infant Temperament: Recommendations For Enhancing Maternal-Infant Bonding - Maulina, Rufidah; Maharani, Alvina Dewi; Nurhidayati, Siti; Wahidah, Nurul Jannatul; Perestroika, Grhasta Dian (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background : The temperament of a baby is one of the characteristics of the baby that plays an important role in the quality of the mother's interaction with the baby. The temperament of a baby significantly influences the quality of the mother's interaction with the baby. The close relationship between a mother’s bonding and her baby’s temperament affects the quality of their interactions. Given the impact of maternal bonding on the regulation of early emotions, it is important to understand how maternal bonding relates to infant temperament. This study aims to investigate the relationship between maternal bonding and infant temperament in the working area of Colomadu II Health Center. Methods : This cross-sectional study involved 102 mothers with babies aged 6 to 11 months in the working area of Colomadu II Health Center. Accidental sampling technique was used for participant selection. The instruments used were the Infant Characteristics Questionnaire (ICQ) and the Mother Infant Bonding Scale-Indonesian (MIBS-I). Tatistical analysis was conducted using the Spearman rank correlations test. Results : The study found that 75.5% of the babies had a mild temperament. The average MIBS-I score for mothers was 1.49 (range: 0-9, SD: 2.038). The Spearman rank correlation test indicated a significant relationship between maternal bonding and infant temperament (p=0.001, < 0.05). Conclusion : This study found a significant relationship between maternal bonding and infant temperament in the working area of Colomadu II Health Center. Recommendations for enhancing maternal-infant bonding are provided.